Development Of Architecture For Pervasive Health Record In Mobile Application - Aris, Farah (2017)
The advancement of the technology has made smartphones as one of the important device that everyone needs. Smartphones can be used as pervasive health records that can access the health records anywhere and anytime.Since 2013,the smartphones ownership rates have skyrocketed in many countries and in Malaysia the percentage have increase 34%.However,with many different mobile's operating system,it makes developing applications in multiplatform is time consuming.This study on'Development of Architecture for Pervasive Health Records in Mobile Application' is a study on of the development of pervasive health records in mobile application that can be used in multi-platforms.The aim of this research is to develop and propose a validated architecture for pervasive health record in mobile application that is used for maintaining pervasive health records using smartphones; and to identifies the best hybrid model and the crucial patient health record datasets to be adopted in the proposed architecture.The objectives on this research firstly is to analyze appropriate mobile health application architecture that could be incorporated in the proposed architecture.Secondly to identifies crucial data needed for doctors when diagnose patients.Thirdly to developed the architecture for pervasive healthcare record in mobile application.Lastly to validate the architecture for pervasive health record in mobile application through the case study.The methodology of this research starts with analyzing the data current research.This include with the study in literature review and case study.The next process is the design and development.The design and development of the prototype will occur in this process.The next process is to validate the architecture and when the architecture has been validated,the process will stop and if the architecture does not validate the process will go to the start.In the process of validation,the prototype has been tested in the real-life situation.The prototype is developed to facilitate patients to retrieve and access their own healthcare records.Therefore,student of UTeM have been asked to test the prototype and they have been questioned their opinion about the prototype.From the results of Cronbach's Alpha it showed that the students are satisfied with the prototype.From the research,the prototype facilitates patients with the medical records that could be refer to doctor when in consultation. Furthermore,from the data collected from the expert user, a list of important medical datasets has been established.This could be used as guidelines of important medical datasets.The research of the proposed architecture only focuses on patients to monitor their own healthcare records.In the future,this architecture could be used to facilitate doctor to diagnose patients anywhere and anytime.